Soluble epoxide hydrolase inhibitor, TUPS, protects against isoprenaline‐induced cardiac hypertrophy. (25th March 2013) - Althurwi, Hassan N; Tse, Mandy MY; Abdelhamid, Ghada; Zordoky, Beshay NM; Hammock, Bruce D; El‐Kadi, Ayman OS
Abstract : Background and Purpose: We have previously shown that isoprenaline‐induced cardiac hypertrophy causes significant changes in the expression of cytochromes P450 (CYP) and soluble epoxide hydrolase (sEH) genes. Therefore, it is important to examine whether the inhibition of sEH by 1‐(1‐methanesulfonyl‐piperidin‐4‐yl)‐3‐(4‐trifluoromethoxy‐phenyl)‐urea (TUPS) will protect against isoprenaline‐induced cardiac hypertrophy. Experimental Approach: Male Sprague–Dawley rats were treated with TUPS (0.65 mg kg −1  day −1, p.o.), isoprenaline (5 mg kg −1  day −1, i.p.) or the combination of both. In vitro  H9c2 cells were treated with isoprenaline (100 μM) in the presence and absence of either TUPS (1 μM) or 11, 12 EET (1 μM). The expression of hypertrophic, fibrotic markers and different CYP genes were determined by real‐time PCR. Key Results: Isoprenaline significantly induced the hypertrophic, fibrotic markers as well as the heart to body weight ratio, which was significantly reversed by TUPS. Isoprenaline also caused an induction of CYP1A1, CYP1B1, CYP2B1, CYP2B2, CYP4A3 and CYP4F4 gene expression and TUPS significantly inhibited this isoprenaline‐mediated effect. Moreover, isoprenaline significantly reduced 5, 6‐, 8, 9‐, 11, 12‐ and 14, 15‐EET and increased their corresponding 8, 9‐, 11, 12‐ and 14, 15‐dihydroxyeicosatrienoic acid (DHET) and the 20‐HETE metabolites. TUPS abolished these isoprenaline‐mediated changes in arachidonic acid (AA) metabolites. In H9c2 cells, isoprenaline caused a significant induction of ANP, BNP and EPHX2 mRNA levels. Both TUPS and 11, 12‐EET significantly decreased this isoprenaline‐mediated induction of ANP, BNP and EPHX2. Conclusions and Implications: TUPS partially protects against isoprenaline‐induced cardiac hypertrophy, which confirms the role of sEH and CYP enzymes in the development of cardiac hypertrophy.